Prenatal stress alters sensitivity to benzodiazepines in adult rats. (30th March 2015) - Lakehayli, S.; Said, N.; Battas, O.; Hakkou, F.; Tazi, A.
Highlights: Prenatal stress leads to a greater propensity toward drug-seeking behavior. Prenatal stress enhances diazepam conditioned place preference. Prenatal stress increased sensitivity to the anxiolytic effects of diazepam. Abstract: In rats, prenatal stress (PS) induces persistent changes in the brain that eventually can be translated in altered behavior leading to a greater consumption of psychostimulants in the offspring during adulthood. Though many studies have been carried on the effects of PS on stimulant drug responsiveness, little is known about susceptibility to benzodiazepines dependence in this animal model. We hereby examined the long-lasting impact of PS exposure during the last 10 days of pregnancy on the vulnerability to benzodiazepine addiction in adult rats. In addition, we also investigated the link between PS and the sensitivity to anxiolytics. Our results reveal that PS offspring exhibited a significantly greater preference to the diazepam-paired side than control offspring in the conditioned place preference. Importantly, we found that PS enhanced the anxiolytic effects of diazepam in the elevated plus maze paradigm. This work demonstrates that PS increased the abuse potential of benzodiazepines and the sensitivity to anxiolytic drugs in offspring of stressed mothers. Thus, investigating the interactions among addiction and PS may contribute to a better understanding how early life events modify neural circuitry and thereby behavior.